2008
DOI: 10.1097/dbp.0b013e318173a575
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Studies on Early Development, Cognition, and Psychosocial Well-Being in Children Born After In Vitro Fertilization

Abstract: Psychological functioning of those born after IVF is reassuring. However, follow-up should be continued and studies should focus on specific cognitive abilities, school performance, and emotional functioning in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
1
26
2
1
Order By: Relevance
“…By means of the (Bayley, 1993;van der Meulen et al, 2002) or the Wechsler Intelligence Scales (WIS) (Wechsler, 1974;1990;1995;van der Steene et al, 1986), neither delayed mental development nor worsening IQ scores between the ART children and the control group were found (Gibson et al, 1998;Leslie et al, 2003;Place and Englert, 2003;Papaligoura et al, 2004;PonjaertKristoffersen et al, 2004;Mu et al, 2006;Nekkebroeck et al, 2008a). In addition, another four studies (Golombok et al, 1996;Wagenaar et al, 2008a;Ludwig et al, 2009a) focusing on cognitive abilities found comparable achievement between the ART and NC groups by using the standardized test. The conclusion drawn is that there was only one report that presented a lower IQ score in the ART group, and the majority of the investigations showed similar cognitive development between the ART children and the control group.…”
Section: Cognitive Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of the (Bayley, 1993;van der Meulen et al, 2002) or the Wechsler Intelligence Scales (WIS) (Wechsler, 1974;1990;1995;van der Steene et al, 1986), neither delayed mental development nor worsening IQ scores between the ART children and the control group were found (Gibson et al, 1998;Leslie et al, 2003;Place and Englert, 2003;Papaligoura et al, 2004;PonjaertKristoffersen et al, 2004;Mu et al, 2006;Nekkebroeck et al, 2008a). In addition, another four studies (Golombok et al, 1996;Wagenaar et al, 2008a;Ludwig et al, 2009a) focusing on cognitive abilities found comparable achievement between the ART and NC groups by using the standardized test. The conclusion drawn is that there was only one report that presented a lower IQ score in the ART group, and the majority of the investigations showed similar cognitive development between the ART children and the control group.…”
Section: Cognitive Developmentmentioning
confidence: 99%
“…Some studies have been conducted to estimate the psychological well-being of IVF children who were close to their 18th birthday (Wagenaar et al, 2008a;Owen and Golombok, 2009), but, till now, few have focused on adolescent born following other technologies, such as ICSI, PGD/PGS, or IVM. Besides, the higher risk of autism reported in ICSI children calls for more research and long-term follow-up.…”
Section: Suggestions In Further Researchesmentioning
confidence: 99%
“…Studies of older children and adolescents conceived via ART also reported various psychological health problems, disorders of behavioral and emotional development (Klemetti et al, 2006), and externalizing and more withdrawn and depressed behaviors (cf. Knoester et al, 2008;Wagenaar, Huisman, Cohen-Kettenis, & Delemarre-van de Waal, 2008), and cognitive delays (Ponjaert-Kristoffersen et al, 2005;Sandin, Nygren, Iliadou, Hultman, & Reichenberg, 2013). However, no differences of mental and psychomotor abilities were found in comparing 2 year-olds who were conceived using ICSI and without the use of ART (Nekkebroeck, Bonduelle, Desmyttere, Van den Broeck, & Ponjaert-Kristoffersen, 2008).…”
Section: Risks Of Art Usementioning
confidence: 52%
“…Previous studies have compared ART to naturally conceived offspring through an examination of ‘obstetric, perinatal, neonatal, post-neonatal outcomes’ (15), ‘chromosomal aberrations’ (16), ‘congenital malformations’ (17), ‘growth and metabolic disorders’ (6) or ‘motor, neurological, cognitive and socio-emotional development’ (18). Recent reviews (2, 6, 11) have concluded that, despite the dearth of evidence, neurological, developmental and psychological outcomes of ART- and naturally-conceived offspring appear to be comparable; by contrast, excess morbidity in the ART population has been primarily attributed to perinatal outcomes, congenital anomalies and imprinting diseases such as Langerhan’s histiocytosis (11), Prader-Willi (19), Angelman (11) and Beckwith-Wiederman (11) syndromes.…”
Section: Discussionmentioning
confidence: 99%